Relation between the HIV and the re-emerging syphilis epidemic among MSM in Germany: an analysis based on anonymous surveillance data. Issue 6 (2nd December 2005) - Marcus, U; Kollan, C; Bremer, V; Hamouda, O
Abstract : In 2003, for the first time since the introduction of highly active antiretroviral therapy (HAART), the number of newly diagnosed HIV infections in Germany increased considerably compared to the previous year. The increase was largely restricted to men who have sex with men (MSM) from larger cities. In this group the number of newly diagnosed HIV infections increased about 30% compared to 2002. Since the late 1990s syphilis infections among MSM also increased in Germany, concentrated in larger cities.